The use of onestep nucleic acid amplification (OSNA) and tumour related factors in the treatment of axillary breast cancer: A predictive model. Issue 5 (May 2016) - Banerjee, S.M.; Williams, N.R.; Davidson, T.I.; El Sheikh, S.; Tran-Dang, M.; Davison, S.; Ghosh, D.; Keshtgar, M.R.S.
Abstract: Aims: We aimed to determine the effectiveness of CK19 mRNA copy number and tumour related factors in predicting non-sentinel axillary nodal involvement, in order to facilitate the formulation of local treatment guidelines for axillary clearance (ANC) following intra-operative analysis of the sentinel node biopsy (SNB) using one-step nucleic acid amplification (OSNA). Methods: Patients due to have (SNB) at our institution for breast cancer as well as patients with high grade ductal carcinoma in situ with pre-operative negative assessment of the axilla were included. Alternate slices of each node were sent for assessment by either OSNA or histopathology. Immediate ANC was performed if OSNA was positive. The CK19 mRNA nodal copy number, the total tumour load (TTL) measured by summation of mRNA copy numbers of all positive nodes, the nodal status at ANC and tumour characteristics for each patient were recorded. A model of risk probability was constructed using TTL and tumour related factors. Results: 664 nodes were analysed from 425 patients who had SNB performed between 2011 and 2014. ANC was performed on 105 of these patients. The concordance between OSNA and histology was 91.4% and negative predictive value (NPV) was 97%. TTL (p = 0.003) and LVI (p = 0.04) were identified as risk factors for non-sentinel nodal involvement. The risk probability model identified all patients with pN2 disease for ANC. Conclusion: In the future a decision to perform ANC will be based on a risk stratification model based on TTL and tumour related factors.